A novel method to join carbon nanotube fibers with metal substrates. (December 2017) - Zhao, Chunfeng; Luo, Zhen; Ao, Sansan; Feng, Mengnan; Liu, Weidong; Zhang, Rui
Abstract: Electrical and electronic applications of carbon nanotube (CNT) fibers require new methods to join them with other live parts of the circuits electrically and mechanically. In this study, the meniscus-confined localized electrochemical deposition (LECD) from a simple aqueous electrolyte was developed as a feasible method to precisely join CNT fibers with copper substrates in an open air environment successfully. During the LECD process, the meniscus remained stable without extending along the fiber surface. The deposited joints have regular shapes and clear boundaries with sizes close to the dispensing nozzle size. The copper deposit with a uniform and compact microstructure clings tightly to the fiber surface, with a distinct interface forming between the copper deposit and the fiber, even though the fiber surface is uneven. The original CNT network morphology remains largely unaffected. The joint surface roughness can be as low as 79.67 nm. The electrical resistance of an individual joint was evaluated to be 1.35 Ohms. With thick enough copper deposit, it can be considered that the joint has a tensile strength of more than 200 MPa. Moreover, this joining method has showed a considerable tolerance for the initial gap between the fiber and the substrate surface. Graphical abstract: